You would add them all and then decide them by how many numbers there are witch would be 3.
2.22. 3/6.46 =2.1533
2.14.
+2.10
———
6.46
The answer is 7.
f(a) = 2a-1, 3f(a) = 3(2a-1) = 15 -> a=2 so f(2a)=f(4)=7
Since y=3x+15
sub 3x+15 for y in other equation
2x+3(3x+15)=1
2x+9x+45=1
minus 45
11x=-44
divide 11
x=-4
sub
y=3x+15
y=3(-4)+15
y=-12+15
y=3
(-4,3)
Answer:
y = 5
Step-by-step explanation:
Step 1: Write equation
-(4y + 2) - (-3y - 6) = -1
Step 2: Solve for <em>y</em>
- Distribute: -4y - 2 + 3y + 6 = -1
- Combine like terms: -y + 4 = -1
- Subtract 4 on both sides: -y = -5
- Divide both sides by -1: y = 5
Step 3: Check
<em>Plug in y to verify it's a solution.</em>
-(4(5) + 2) - (-3(5) - 6) = -1
-(20 + 2) - (-15 - 6) = -1
-22 - (-21) = -1
-22 + 21 = -1
-1 = -1
My math teacher time me is easier to do it after